Enhanced tribocatalytic degradation of dye pollutants through governing the charge accumulations on the surface of ferroelectric barium zirconium titanate particles. (September 2022) - Tang, Qing; Zhu, Mengde; Zhang, Hongfang; Gao, Ju; Kwok, Kin Wing; Kong, Ling-Bing; Jia, Yanming; Liu, Laijun; Peng, Biaolin
Abstract: The phenomenon triboelectricity has recently been demonstrated great potentials for mitigating environmental pollutions. In this study, with the aim of investigating the crucial parameters for the phenomenon, a typical perovskite ferroelectric micron-sized Ba(Zr0.05 Ti0.95 )O3 (BZT) particle has been fabricated as a tribocatalyst by the conventional solid state method for degrading the common organic dye pollutants such as rhodamine B (RhB), methylene blue (MB) and methyl orange (MO) via magnetic stirring. Our results show that the accumulation of triboelectric charges on the micron-sized particle surfaces is crucial for inducing high performances of the tribocatalysis. Various experimental parameters such as surface roughness of the reaction vessel, triboelectric charge density (TECD) and polarization states of the ferroelectric tribocatalyst have also been shown important for achieving the strong tribocatalytic activity. A high kinetic rate constant of 0.4482 h −1 (or 100% degradation in 7 h) has been achieved in the degradation of RhB using poled micron-sized BZT particles stirred with polytetrafluoroethylene (PTFE) magnetic bars (which can generate a high TECD). The enhanced ferroelectricity and tilted bandgap of the tribocatalyst caused by a higher nanodomain density and dielectric screening phenomenon through the poling treatment have been considered in elucidating the high performance engendered by the ferroelectric tribocatalyst. Graphical Abstract: ga1 Highlights: The tribocatalytic activity is dependent on the triboelectric charges accumulation. The poling treatment can increase a higher nanodomain density. The degradation is strongly related to the triboelectric charge density. The dielectric screening phenomenon can tilt the energy band.